Centering female agency while investigating contraceptive use: a case study in Agincourt, South Africa - Cara Margherio (BMC, 2019)
Abstract Background Rural areas of South Africa face persistently high teenage and premarital childbearing rates, reflecting a lack of or inconsistent use of modern contraception. In attempting to understand this behavior, much of the literature has denied agency to young women, portraying them solely as victims of their environments. This study moved beyond these approaches to understanding adolescent contraceptive use, to reframe the investigation to focus on the tension around exercising agency within specific structural constraints. Methods Findings are based on a qualitative study in Agincourt, South Africa. Data were collected through six focus group discussions with 63 women aged 18-44. A grounded theory approach utilizing emergent coding was performed focusing on the decision-making processes around family planning. The focus group participants discussed attitudes and norms around: early first births, contraceptive use, unplanned pregnancy, abortion, and HIV testing. When possible, differences that emerged around these topics according to the age groups (18-24, 25-34, and 35-44) and/or nationality of village (South African or Mozambican) are highlighted. Results Participants of all focus groups agreed that early first birth were common and undesirable. Younger participants described pregnancy prevention as a key rationale for contraceptive usage, while older participants were more inclined to cite HIV prevention. Women of all focus groups discussed the importance of women taking the initiative with family planning. Participants expressed a range of opinions about the acceptability of abortion, and all focus groups discussed concerns about the safety of abortion. Finally, all of the focus group participants stressed the importance of HIV testing, both to protect themselves and to protect their families. Conclusion This study found many locations of agency for young women in rural South Africa. The decision-making surrounding contraceptive use consists of a series of decision junctures at which women must assign values to certain factors and then select their behavior on the basis of those values. Young women weigh the costs and benefits of contraception and of pregnancy, while also taking into account the chances of actually becoming pregnant along with the costs and benefits of abortion. Furthermore, the women explicitly viewed contraception as within their own realm of decision-making and action (as opposed to within the realm of their male partners).